Soluble CD72, is a T-cell activator probably via binding to CD6 in homeostasis and autoimmunity - Eiza, Nasren; Sabag, Adi; Kessler, Ofra; Toubi, Elias; Vadasz, Zahava (Frontiers in Immunology, 2024)
Background CD72 is a highly required regulatory molecule in B cells. Its sufficient expression is crucial for maintaining self-tolerance. In contrast, soluble CD72 (sCD72) is reported to be increased in the serum of autoimmune diseases such as systemic lupus erythematosus and primary Sjogren’s syndrome (pSS). Objective We wanted to assess the biological effect of sCD72 on CD4+T cells. Methods We performed mass spectrometry and co-immunoprecipitation experiments to look for a sCD72 receptor on activated CD4+T cells. Afterward, to explore the biological functions of sCD72, we used flow cytometry for the cytokine secretion profile, a phosphorylation assay for the signaling pathway, and a CFSE dye-based assay for cell proliferation. Results We found and validated the sCD72 and CD6 interaction as a possible ligand-receptor interaction. We also demonstrated that sCD72 significantly increases the expression of pro-inflammatory cytokines, namely IL-17A and IFN-γ, in activated CD4+T cells and increases the proliferation of CD4+T cells, possibly through its activation of the SLP-76-AKT-mTOR pathway. Conclusion The sCD72-CD6 axis on activated CD4+T cells is probably a new signaling pathway in the induction of immune-mediated diseases. Therefore, targeting sCD72 may become a valuable therapeutic tool in some autoimmune disorders.